Novel t(5;19) Translocation in a Patient with PDGFRB Associated Chronic Leukemia: Implications for Treatment Strategy - Joel D. Provenzano; J. Phillip Kuebler (Case Reports in Hematology)
Myeloproliferative disorders are variable disorders, based on the genetic abnormality present and the cell line progenitors that are affected. In this case, we discuss a novel gene translocation in the subset of PDGFRB mutations, first seen with prominent hyperbasophilia. This case demonstrates the possibility for lower therapeutic doses of imatinib mesylate than previously reported, in order to control leukocyte counts and reverse the genetic mutation.